Scaling-up short food supply chains? A survey study on the drivers behind the intention of food producers. (April 2017) - Aggestam, Vivianne; Fleiß, Eva; Posch, Alfred
Abstract: The growing interest for alternative food initiatives has ignited the debate on scaling-up such initiatives. Empirical studies on such initiatives tend to ignore the underlying psychological constructs that affect farmers' intentions and decisions. This paper investigates the intention to scale-up their businesses in Sweden based on a survey of 338 Short Food Supply Chain producers utilising the construct of the Theory of Planned Behaviour (TPB) as a theoretical framework. The findings show that attitude can be considered the most important driver for their intention to scale-up their business. Also, the perceived level of control and the positive perception of personal referents, i.e. family members, co-workers and consumers, foster their intention to scale-up. In contrast, perceptions of other farmers and competitors as well as the perception of framework conditions (e.g. state support, availability of financial resources) do not have any significant influence. However, several socio-economic characteristics such as size of farm, type of production and use of infrastructure are identified as significant influences. This insight is relevant for the numerous countries experiencing growing interests in alternative food initiatives. Highlights: Implications of short food supply chain initiatives increased demand. Investigating producers' intention to scale-up with the Theory of Planned Behavior. Linear regression analysis identifies attitude as most important driver to scale-up. Perceptions of other farmers and framework conditions show no influence.